2011
DOI: 10.1111/j.1570-7458.2011.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

Gamete number and size correlate with adult size in the egg parasitoid Trichogramma euproctidis

Abstract: International audienceIn parasitoids, the size of the adult is influenced by the size and quality of the host in which it develops. Body size is generally positively correlated with several adult fitness proxies (fecundity, longevity, and mating capacity). The initial resources available to an individual can influence gamete production (sperm and oocytes), and the number and quality of gametes produced directly influence the expected fitness of both males and females. Gamete production in relation to adult bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…The reduction in sperm number thus seems to be relatively more important than the reduction in size; at least when size is estimated using tibia length. Sperm length was not influenced by the size of the adult male in A. listronoti contrarily to what is reported in T. euproctidis (Durocher-Granger et al, 2011;Martel et al, 2011). In T. euproctidis, sperm length was shown to influence the probability of exiting the spermatheca, small sperm being favored in the race for fertilizing the oocyte (L. Durocher-Granger unpublished data).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The reduction in sperm number thus seems to be relatively more important than the reduction in size; at least when size is estimated using tibia length. Sperm length was not influenced by the size of the adult male in A. listronoti contrarily to what is reported in T. euproctidis (Durocher-Granger et al, 2011;Martel et al, 2011). In T. euproctidis, sperm length was shown to influence the probability of exiting the spermatheca, small sperm being favored in the race for fertilizing the oocyte (L. Durocher-Granger unpublished data).…”
Section: Discussionmentioning
confidence: 50%
“…A reduction in fecundity with a reduction of size of the female has been observed in most parasitoid species studied (Honek, 1993;Mills and Kuhlmann, 2000;Durocher-Granger et al, 2011) including several Mymaridae species (Cronin and Strong, 1996;Jepsen et al, 2007;Irvin and Hoddle, 2009) (but see Riddick, 2005a for a counter example). Our study suggests a decrease in fitness in small females with a reduced maximum capacity for egg production (Parker and Begon, 1986).…”
Section: Discussionmentioning
confidence: 92%
“…The quality of the males available and the number of previous mates they had will then influence the capacity of the females to react as predicted by the local mate competition model and the host-quality model. Sperm production can incur sizable costs for the males and they should be under selection pressure to optimise their use of it (Martel et al, 2008;Durocher-Granger et al, 2011). After several matings, males may exhaust their sperm supply, permanently so in species in which males emerge with their full sperm complement but produce none during their adult life (prospermatogenic), but temporarily in species in which males produce some sperm throughout their life (synspermatogenic) (Boivin et al, 2005;Boivin & Martel, 2012).…”
Section: Optimality Models In Biological Control 7 Optimal Sex Ratiomentioning
confidence: 99%
“…Hind tibia length reflects body size of Trichogramma. The larger the individual is, the more the egg load is, and the stronger the parasitic capacity is (Durocher-Granger, Martel, & Boivin, 2011;Thorne, Pexton, Dytham, & Mayhew, 2006). Pavlik (1993b) found that based on wasp species or different strains, the body size of Trichogramma wasps could be used to assess Trichogramma quality.…”
Section: Discussionmentioning
confidence: 99%